Effects of Lime and Organic Amendments Derived from Varied Source Materials on Cadmium Uptake by Potato. Issue 4 (1st July 2017) - Al Mamun, Shamim; Lehto, Niklas J.; Cavanagh, Jo; McDowell, Richard; Aktar, Munmun; Benyas, Ebrahim; Robinson, Brett H.
Abstract : Repeated applications of Cd‐rich phosphate fertilizers have resulted in elevated concentrations of this toxic element in some New Zealand soils. Exceedance of the food safety standard for Cd (0.1 mg kg −1 fresh weight) has been reported for potato ( Solanum tuberosum L.). Composts may efficiently sorb Cd in soil and therefore reduce its phytoavailability, leading to reduced uptake by plants. We aimed to determine the potential of various composts, shredded corn stover, and lime at two different rates to reduce the transfer of Cd from a soil (containing 1.45 mg kg ‐1 Cd) to potato (var. 'Nadine'). In the control, the peeled tubers, skins, leaves, and stems had Cd concentrations of 0.04, 0.09, 0.26, and 0.53 mg kg ‐1 dry weight, respectively. There was a 71% reduction in tuber Cd concentrations in potatoes grown in soil amended with 5% (w/w) shredded corn stover, although it significantly decreased potato biomass. Potatoes grown in soil amended with pig manure compost, mushroom compost, sawdust‐animal waste compost, and municipal compost at rates of either 2.5 or 5% (w/w) reduced tuber Cd concentrations by 58 to 66%, 46 to 63%, 52 to 53%, and 29 to 49%, respectively. Lime (1.3%) application in soil reduced tuber Cd concentrations by 50%. Composts significantly increased tuber biomass. Further work is warranted to identify the key components of composts that result in reduced Cd uptake by plants. Core Ideas: Composts made from contrasting source materials reduced Cd uptake by potatoes. Unlike lime, composts did not result in reduced micronutrient uptake. Composts resulted in a greater biomass increase than lime.